Role of aspirin, beta-blocker, statins, and heparin therapy in septic patients under mechanical ventilation: a narrative review - Lou'i Al-Husinat; Amer Abu Hmaid; Hadeel Abbas; Batool Abuelsamen; Mutaz Albelbisi; Said Haddad; Ibrahim Qamileh; Ossaid Quneis; Zaid Jehad Al Modanat; Giuseppe Ferrara; Fernando Suparregui Dias; Gilda Cinnella (Frontiers in Medicine, 2023)
Sepsis is the main cause of death among patients admitted to intensive care units. Management of sepsis includes fluid resuscitation, vasopressors, intravenous antimicrobials, source control, mechanical ventilation, and others. New insights into the potential benefits of non-antimicrobial drugs in sepsis have evolved based on the pathophysiology of the disease and the mechanism of action of some drugs, but the findings are still controversial. In this study, we aimed to evaluate the effect of beta-blockers, aspirin, statins, and heparin as adjunctive treatments in septic patients under mechanical ventilation with non-cardiovascular diseases and their effect on mortality. We searched PubMed with relevant keywords (beta-blockers, aspirin, statins, or heparin, and critically ill or sepsis) for the last 10 years and some personal collection of relevant articles, and then we assessed studies according to prespecified inclusion and exclusion criteria. Our results show that beta-blockers, aspirin, and heparin may have promising feedback on reducing mortality. However, new well-controlled, randomized, multicenter studies are needed to confirm that, and multiple issues regarding their usage need to be addressed. On the other hand, the feedback regarding the effectiveness of statins was not as strong as that of the other drugs studied, and we suggest that further research is needed to confirm these results.